Mediation in the Settlement of Inheritance and Joint Property Matters in the Medan Religious Court - Sitompul, Ariman; Gayo, Sabela; Mary, Dina (International Asia Of Law and Money Laundering, 2024)
Conflict or dispute always exists in every human relationship in social interaction, common property is a thing that often triggers conflict in the family is known that not a few cases of conflict which resulted from the inheritance that goes to court. Disputes generally occur regarding rights and obligations that are classified in civil conflict issues can be resolved one of them by mediation both out of court and in court. Mediation in the settlement of civil cases can conducted at the beginning of litigation as well as during litigation against inheritance claims, joint property claims. Solution dispute specifically has the meaning that the dispute between husband and wife differences of opinion between the two parties due to property can also refer to disputes so that over this there is an imbalance ownership and need a good mediation process to equalize the position for both parties. This study aims to explain the legal power of mediation in court proceedings Religion Medan, the second to know the procedures for the division of inheritance and joint property according to compilation of Islamic law. Type of research used is empirical legal research with approach juridical sociological. The Data used is sourced from primary and secondary legal data analyzed qualitatively. The results of this study indicate that the legal power of mediation in the trial process in the Religious Court of Medan, namely with the deed of peace, the result of the peace agreement received legal certainty, the second division of common property according to the compilation of the law Islam is a husband or wife gets the same half because it is also seen based on taste fairness or good faith of one of the parties.